2008
DOI: 10.1007/s00330-008-0920-2
|View full text |Cite
|
Sign up to set email alerts
|

Significance of sagittal reformations in routine thoracic and abdominal multislice CT studies for detecting osteoporotic fractures and other spine abnormalities

Abstract: The purpose was to assess osteoporotic vertebral fractures and other spinal lesions in sagittal reformations obtained from routine multidetector computed tomography (MDCT) studies of the thorax and abdomen, to compare sagittal reformations with axial images in detecting these lesions and to investigate how frequently they were missed in the official radiology report. Routine abdominal or thoracoabdominal MDCT using a standard protocol was performed in 112 postmenopausal women. Axial images and sagittal reforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…In the past few years, several imaging techniques have been proposed for the detection of VFs [7,8]. Spine assessment with the aim of VF detection has been performed on the main basis of spine radiographs and dual-energy X-ray absorptiometry scans [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, several imaging techniques have been proposed for the detection of VFs [7,8]. Spine assessment with the aim of VF detection has been performed on the main basis of spine radiographs and dual-energy X-ray absorptiometry scans [9].…”
mentioning
confidence: 99%
“…Results show that detection is still low when VFs are not the intent of the study [13,14]. Radiographs of the chest and abdomen, as well as CT sagittal multiplanar reconstructions (MPRs), have been considered [7,8,15,16] following the widespread use of CT imaging. In recent years, the opportunity to screen for VFs on ancillary sequences of advanced imaging techniques, such as localisation scans of CT and MRI, were also investigated [17][18][19].…”
mentioning
confidence: 99%
“…The measurements of the anterior, median and posterior vertebral heights yielded quantitative variables whose ratios give the percentages of loss of vertebral heights (Genant et al, 1996;Muller, 2008;Kim et al, 2012;Oei et al, 2013;Takada et al, 1998;Alacreu et al, 2017).…”
Section: Figure 1 Schematic Representation Of Measurementsmentioning
confidence: 99%
“…Although often detected incidentally by imaging explorations performed for other purposes. Despite the ease of identifying vertebral fractures in computer tomography scanner (CT, TDM or CT scanner), assessment of vertebrae in axial sections only instead of sagittal sections are source of under diagnosis and under reporting of vertebral fractures (Lenchik et al, 2004;Bauer et al, 2006;Muller et al, 2008;Muller et al, 2008;Woo et al, 2008;Williams et al, 2009). The detection is improved by scanner using lateral vieuw or radio mode with limited success or sagital reconstructions (Genant et al, 1996;Muller, 2008;Kim et al, 2012;Oei et al, 2013;Takada et al, 1998;Takada et al, 2013;Alacreu et al, 2017;Glinkowski et al, 2017;Gausden et al, 2017;Lee et al, 2017) and some authors reported newly introduced automated detection and soft-ware assisted systems (Narloch et al, 2016;Burns et al, 2017 to osteoporosis, the scarcity of data available on osteoporosis and practically non-existence and lack of the data on vertebral fracture incidence in these region and countries (IOF study group, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In daily clinical practice, MD-CT is routinely used in a wide variety of patients for clinical indications which are unrelated to osteoporotic fractures. Müller et al assessed, amongst other questions, osteoporotic vertebral fractures on sagittal reformations of routine MD-CT-scans of the chest and/or abdomen in 112 postmenopausal women [20]. The authors article in Eur Radiol, published by Springer discovered osteoporotic fractures in 27 patients of which none were mentioned in the radiology report; only six of these osteoporotic fractures were identifiable on routine axial CT images.…”
Section: Imaging Of Osteoporosismentioning
confidence: 99%